2016
DOI: 10.1302/2058-5241.1.000007
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of medial knee ligament injuries: current indications and techniques

Abstract: The medial collateral ligament (MCL) and the posterior oblique ligament (POL) are the main static valgus restraints of the knee.Most isolated medial injuries can be treated with bracing and early knee motion.Combined MCL and ACL (anterior cruciate ligament) injuries can be managed with bracing of the knee followed by a delayed reconstruction of the ACL.Residual medial laxity may be addressed at the time of ACL surgery.Bony avulsions, incarceration of the distal MCL under the meniscus or over the pes anserinus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Previous authors reported that in the set of a reconstruction the POL should be fixed in full extension 13 ; however, our attempt to reattach the POL in flexion is based on the fact that the present technique is a repair of a isometric structure which doesn't have the same biomechanical repercussions as in a reconstruction (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors reported that in the set of a reconstruction the POL should be fixed in full extension 13 ; however, our attempt to reattach the POL in flexion is based on the fact that the present technique is a repair of a isometric structure which doesn't have the same biomechanical repercussions as in a reconstruction (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…An avulsion of the MCL from the distal tibial insertion is 1 such example. 4 , 9 , 10 , 11 , 12 Unfortunately, the majority of literature discussing nonoperative and surgical management of MCL injuries does not distinguish the site of ligamentous injury, making the true incidence and associated treatment outcomes of distal injuries difficult to discern. Nevertheless, there is evidence to suggest that distal tibial MCL injuries do not do well with conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few surgical indications for an acute repair or reconstruction of an isolated or concomitant MCL injury is an avulsion from the distal tibial insertion ( Fig 1 ). 4 , 9 , 10 , 11 , 12 When the distal insertion is ruptured, the MCL fibers can retract and displace superficial to the pes tendon, becoming a Stener-type lesion. Alternatively, the ligament can retract so much that it becomes incarcerated into the medial joint space.…”
mentioning
confidence: 99%
“…Nevertheless, we tried to summarize MSC injuries management (Figure 2, Figure 3) according to the most currently agreed. [3][4][5][6]8,10,11,13,17,24,34,35,[39][40][41][42][43] In any acute injury, the first step is to let the soft tissues rest and provisionally stabilize the knee until it is possible to make a proper diagnosis. Consequently, pain management, application of a hinged knee brace limiting ROM to 0-30º of flexion, touch toe weight-bearing (WB), and avoiding ER of the foot is recommended.…”
Section: Management Of Msc Injuriesmentioning
confidence: 99%